Pembelajaran Matematika Dengan Pendekatan Inkuiri Terbimbing Untuk Meningkatkan Kemampuan Pemahaman Dan Komunikasi Matematis Siswa Sekolah Menengah Pertama - Sri Lindawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The aim of this research is to analysis the difference significance in enhancingbetween student’s mathematical understanding and communication from a pretest-posttestexperimental control group design by using Guide Inquiry Approach Learning (PIT) andConventional Approach (PK). This study involving VII th grader Junior High School inBandung, West Java. The result of the research show that : (1) Guide Inquiry ApproachLearning (PIT) significantly were better to enhance mathematical understanding andcommunication compare to approach learning dan students’ mathematical ability category;(2) There was no interaction between approach learning factor and students’ mathematicalability category in enhancing students’ mathematical understanding, but there was interactionbetween approach learning factor and students’ mathematical ability category in enhancingstudents’ mathematical communication; (3) Student’s scale shown that more student’s havepositive perspective toward Guide Inquiry Approach Learning.